Bad Mothers: Kristeva and the Undoing of the Natural Maternal? - Sjöholm, Cecilia (Acta Nova Humanistica: A Journal of Humanities Published by New Bulgarian University, 2024)
One of the most sensitive representations in cultural, moral and political discourses is that of motherhood. The idea that a mother would feel estranged from her child, or even regret having a child, is a taboo that has only begun to be considered in the twenty-first century. What is a "bad" mother, how and why are idealized representations of motherhood now being questioned? In this analysis, the work of Julia Kristeva stands at the forefront. Through her reworking of Melanie Klein’s object theory above all, Kristeva challenges "natural" motherhood as a fetishized construct. Most importantly, Kristeva’s theory of the abject presents a critique of the fetishization of motherhood and its entwinement with consumer society. This essay mobilizes Kristeva to analyze fictional and cinematic works by Rachel Cusk and Maggie Gyllenhaal concerned with the undoing of idealized ideas of motherhood. Cusk’s novel A Life’s Work (2001) offers an autofictional narrative of her first experience of motherhood, one of boundlessness, exasperation, sleeplessness and fear; of fluids, smells and noise. Unable to fulfill her daughter’s needs, unfulfilled herself, critical of her environment and her peers, she provides witness to an alienated experience, that of a "bad" mother. Further, in Cusk’s novel, this is intimately connected to the development of consumer society and its mythology of motherhood. For its part, Gyllenhaal’s film The Lost Daughter, which adapts a novel by Elena Ferrante, tells a story of abjection at the edge of the loss of self, and puts the question of what it means to be a "natural" mother in focus. Having recourse to theories of the object in capitalism, assisted by C. B. McPherson and Sigmund Freud, this essay argues for the contemporary significance of Julia Kristeva’s work in the face of fantasies about motherhood in capitalist society.